2012
DOI: 10.1099/mic.0.058867-0
|View full text |Cite
|
Sign up to set email alerts
|

A fungal homologue of neuronal calcium sensor-1, Bbcsa1, regulates extracellular acidification and contributes to virulence in the entomopathogenic fungus Beauveria bassiana

Abstract: A fungal homologue of neuronal calcium sensor-1, Bbcsa1, regulates extracellular acidification and contributes to virulence in the entomopathogenic fungus Beauveria bassiana gene expression and other biological processes. The filamentous fungus Beauveria bassiana is a broad-host-range pathogen of insects that acidifies the extracellular milieu during growth and pathogenesis towards target hosts. A collection of B. bassiana random insertion mutants were screened on pH indicator plates and one mutant was isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Sequestration of nutrients including Fe 2+ and surface exposure to sunlight, act as nutrient and oxidative stressors, respectively, and penetration through the cuticle and then interaction with immune responses include exposure to further oxidative stress. The nature of membrane carbohydrates, the production of acidic metabolites including oxalate, and use of cytochrome P450s capable of assimilating host hydrocarbons contribute to attachment and degradation of the host epicuticle (Fan et al 2012;Kirkland et al 2005;Pedrini et al 2010;Zhang et al 2011a. Chitinases, protease, and lipases, along with mechanical pressure allow further ingress (Ortiz-Urquiza and Keyhani 2013).…”
Section: Conclusion and Future Directions: Stress And Virulencementioning
confidence: 98%
“…Sequestration of nutrients including Fe 2+ and surface exposure to sunlight, act as nutrient and oxidative stressors, respectively, and penetration through the cuticle and then interaction with immune responses include exposure to further oxidative stress. The nature of membrane carbohydrates, the production of acidic metabolites including oxalate, and use of cytochrome P450s capable of assimilating host hydrocarbons contribute to attachment and degradation of the host epicuticle (Fan et al 2012;Kirkland et al 2005;Pedrini et al 2010;Zhang et al 2011a. Chitinases, protease, and lipases, along with mechanical pressure allow further ingress (Ortiz-Urquiza and Keyhani 2013).…”
Section: Conclusion and Future Directions: Stress And Virulencementioning
confidence: 98%
“…Targeted deletion of Msn2 resulted in a strain impaired for growth at low pH, showing defects in virulence and sporulation. The ability to acidify the medium, and in particular production of oxalic acid, is known to contribute to the ability of the fungus to penetrate the insect cuticle (Fan et al 2012b;Kirkland et al 2005), and therefore, loss of this ability may in part account for the observed phenotype seen in the Δmsn2 mutant strain. Finally, the evolutionarily conserved transcriptional cofactor, multiprotein bridging factor 1 (MBF1), which acts as a link between TATAbinding protein (TBP) and transcription factors, has been shown to contribute to the regulation of stress responses and virulence in B. bassiana (Ying et al 2014).…”
Section: Insect and Plant Interactionsmentioning
confidence: 98%
“…Construction and preliminary screening of a B. bassiana random insertion (T-DNA) library has already been reported (Luo et al, 2009). Isolation of fungal genomic DNA and use of YADE to clone fragments flanking the T-DNA insertion site as described (Fan et al, 2012a). All PCR products were cloned into the A-T cloning vector pUCm-T (Bio Basic, Canada) and subsequently sequenced.…”
Section: Nucleic Acid Manipulations and Construction Of δBbmsn2 And Cmentioning
confidence: 99%